Revisiting the structural basis and energetic landscape of susceptibility difference between HLA isotypes to allergic rhinitis. (October 2016) - Mao, Xin-Li; Zhu, Feng; Pan, Zhao-Hu; Wu, Guo-Min; Zhu, Hong-Yuan
Graphical abstract: Highlights: The susceptibility difference between HLA isotypes to allergic rhinitis is investigated. Different HLA isotypes have a low sequence conservation but a high structural similarity. HLA-DR is found to tightly bind AR allergen-derived peptides as compared to HLA-DP and -DQ. HLA-DR is expected to closely associate with the pathological process of AR. Abstract: The human leukocyte antigen class II (HLA II) molecules are implicated in the immunopathogenesis of allergic rhinitis (AR). The HLA II contains three allelic isotypes HLA-DR, -DQ, and -QP that exhibit considerably different susceptibility to AR. Here, we investigated the structural basis and energetic landscape of the susceptibility difference between the three HLA II isotypes to AR by combining computational analysis and experimental assay. Multiple sequence alignment revealed a low conservation among the three subtypes with sequence identity of ∼10% between them, suggesting that the peptide repertoires presented by HLA-DR, -DP and -DQ are not overlapped to each other, and they may be involved in different immune functions and dysfunctions. Structural analysis imparted that the antigenic peptides are rooted on the peptide-binding groove of HLA molecules and hold in a PPII-like helical conformation. Subsequently, the interaction behavior of 17 AR allergen-derived peptides with HLA-DR, −DP and −DQ was investigated using a statistics-based quantitative structure-activity relationship (QSAR) predictor. It was found a significant difference between the binding capabilities of these antigenic peptides to HLA-DR and to HLA-DP/-DQ; the former showed a generally higher affinity than the latter with p -value of 0.02 obtained from 2-tailed Student's t -test. The computational findings were then confirmed by HLA II–peptide stability assay, which demonstrated that the AR allergen-derived peptides have a high in vitro selectivity for HLA-DR over HLA-DP/-DQ. Thus, the HLA-DR isotype, rather than HLA-DP and −DQ, is expected to associate with the pathological process of AR.